A Stable Porous Anionic Metal–Organic Framework for Luminescence Sensing of Ln3+ Ions and Detection of Nitrobenzene. Issue 3 (8th January 2014) - Qin, Jun‐Sheng; Bao, Shao‐Juan; Li, Peng; Xie, Wei; Du, Dong‐Ying; Zhao, Liang; Lan, Ya‐Qian; Su, Zhong‐Min
Abstract A hexagonal channel‐based porous anionic metal–organic framework was successfully constructed. IFMC‐3 is stable in air and acidic/basic aqueous solutions at room temperature, and constitutes a selective luminescent sensing material for Ln3+ ions and a recyclable probe for the sensitive detection of nitrobenzene.